Internalization of Adaptive Capacity and Intrinsic Learning Motivation in Hydroponic Wick-Based Creative Economic Empowerment - Putri Adabiyah; Regia Reha Datul; Aulia Tri Halimah; Rika Fitri Ramadani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the role of motivation and creativity in hydroponic wick system training for youth at PKBM Aruhhama. A qualitative approach was employed through in-depth interviews, observations, and documentation involving three training participants as informants. The findings reveal that intrinsic motivation significantly encouraged participant engagement, as indicated by enthusiastic attendance and active inquiry behavior during the training sessions. Participants who demonstrated higher motivation showed a better understanding of wick system principles and independently explored the Deep Flow Technique (DFT) as an extension of their learning. Creativity was reflected in the participants’ adaptive approaches to applying hydroponics within their household environments, although two participants still required continuous assistance to independently assemble the system. The training program at PKBM Aruhhama effectively introduced hydroponics as a practical skill for urban youth; however, the sustainability of the program depends on post-training support structures such as peer learning groups and structured mentoring. This study highlights the importance of aligning motivational design with creative facilitation in community-based vocational training programs.